Corporate Perspectives in Achieving Sustainable Development Goals (SDGS) Integration with Sustainability Reporting - Prasetiyo, Yudhi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The issue of climate change that continues to hit the world has become the centre of global attention. Indonesia's participation in the SDGs is not only an effort to achieve sustainable development in the global world. The purpose of this study is to observe and explore the Company's perspective on achieving Sustainable Development goals in the Sustainability Report it submits. The method used is a literature study approach from research articles on the same topic for the period 2020-2024. The results of the study indicate that entities are increasingly aware of the importance of the SDGs and support their inclusion in business strategies and sustainability reports. In addition, this study found that factors that determine the success of SDGs implementation include integrated sustainability governance, cross-sectoral collaboration, and a dedicated sustainability officer. The results of this study also show that there is a positive relationship between SDGs implementation and return on equity (ROE) in terms of financial performance. This conclusion suggests that SDGs implementation can provide economic and social benefits if carried out with Strengthening sustainability governance and alignment between reporting and SDGs implementation in corporate strategy are recommendations from this study.